ASSESSMENT OF TRENDS IN THE DEVELOPMENT OF BUSINESS ENVIRONMENT OF UKRAINE IN UNSTABLE CONDITIONS - KARVATSKA, Nataliіa; HONCHARUK, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the article, the authors analyzed the dynamics of the main macroeconomic indicators, such as: indexes of the gross domestic product and industrial production; volumes of exports, imports and foreign trade balance of Ukraine to assess general trends in the development of Ukraine's business environment. The authors considered the results of the survey of company managers conducted by the National Bank of Ukraine in 2023 and the dynamics of the Index of Business Expectations of Enterprises; the results of a joint study conducted by the Innovation Development Center, the Office for Entrepreneurship and Export Development, the Diya.Business national project, the strategic agency Advanter Group, and the dynamics of the Ukrainian Business Index. The causes and consequences of the decline in the economic activity of Ukrainian enterprises in the main sectors of the economy were identified. Rational solutions aimed at supporting and restoring business in conditions of instability were determined. The results of the international assessment based on the ranking of economic freedoms from the American Heritage Foundation (Economic Freedom Index), the Corruption Perceptions Index from Transparency International (Corruption Perceptions Index), and the international study of the perception of national brands from Brand Finance (Global Soft Power Index) were considered. The role of Ukraine in the world economy was defined.It was concluded that the recovery of the Ukrainian economy remains restrained due to significant losses, destruction, and ongoing hostilities. Positive expectations in terms of economic recovery are associated with the further adoption and implementation of EU decisions on: using the advantages of the unification of the energy systems of continental Europe ENTSO-E and Ukraine (the so-called "energy visa-free"); exemption of Ukrainian business products from tariffs and quotas ("economic visa exemption"); liberalization of road transportation ("transport visa-free"); integration of Ukrainian customs authorities with European ones ("customs visa-free"). Such decisions will significantly contribute to the expansion of international trade, further integration of Ukraine into European production, as well as transport and logistics networks.
Keywords: assessment; analysis; business environment; economy of Ukraine; international assessment